Company law - Cheffins, Brian R. (Clarendon Press,Oxford University Press, 1997)
Company Law: Theory, Structure and Operation is the first United Kingdom law text to use economic theory to provide insights into corporate law, an approach widely adopted in the United States. In this book, Brian Cheffins discusses the inner workings of companies, examines the impact of the legal system on corporate activities, and evaluates the merits of governmental regulatory strategies. The book covers core areas of the undergraduate company law syllabus in a stimulating and theoretically enlightening fashion and addresses important company law topics such as: * limited liability of shareholders * shareholders' remedies * corporate governance (including the Cadbury Report) * executive pay (including the Greenbury Report) * the role of self-regulation in United Kingdom securities markets * the impact of European Union Directives on company law in the UK Brian Cheffins also examines in detail a number of questions which have not been fully explored elsewhere. These include: * What are the justifications for legal regulation of company affairs? * What are the drawbacks associated with government intervention? * How can one ascertain the optimal format for company law rules?